Mutational profiling in patients with MDS: Ready for every-day use in the clinic?. Issue 1 (March 2015) - Bacher, Ulrike; Kohlmann, Alexander; Haferlach, Torsten
<x xml:space="preserve">Abstract</x> Multiple recurrent somatic mutations were identified in the majority of patients with myelodysplastic syndromes (MDS), but investigating the broad spectrum of molecular markers in MDS exceeds many laboratories' capacity when traditional molecular techniques are used. High-throughput second generation sequencing (=next-generation sequencing, NGS) has proven to be applicable for comprehensive biomarker mutation analyses allowing to increase diagnostic sensitivity and accuracy and to improve risk stratification and prognostication in addition to cytomorphology and cytogenetic analysis in patients with MDS. Amplicon deep-sequencing enables comprehensive biomarker analysis in a multitude of patients per investigation in an acceptable turn-around time and at affordable costs. Comprehensive myeloid marker panels were successfully introduced into diagnostic practice. Therefore, molecular mutation analysis is ready for use in all patients with suspected MDS, may contribute to risk stratification in possible candidates for allogeneic stem cell transplantation, and should become an integral part of clinical research studies in MDS patients.